Sliding Window Rough measurable function on I- core of triple sequences of Bernstein operator - Deepmala Rai; N. Subramanian (IndoMS, 2019)
We introduce sliding window rough I- core and study some basic properties of Bernstein polynomials of rough I- convergent of triple sequence spaces and also study the set of all Bernstein polynomials of sliding window of rough I- limits of a triple sequence spaces and relation between analytic ness and Bernstein polynomials of sliding window of rough I- core of a triple sequence spaces.